Report of rare genotypes of Acanthamoeba from soil source of the Payeh Maga Highland forest, North-eastern Sarawak, Malaysia - Chan, Li-Li; Toh, Hiu-Ching; Jaikwang, Kantiya; Loo, Ee-Mun; Wong, Jia-Haw; Liew, Yun-Khoon; Ong, Kian-Huat; Ooi, Soo-Shen (Elsevier, 2022)
Pathogenic Acanthamoeba species are the causative agents of Acanthamoeba keratitis and granulomatous amoebic encephalitis. Members of this amoeba genus are ubiquitous in the environments. In Malaysia, most environmental studies performed to date have targeted the detection and characterisation of Acanthamoeba sp. in different water sources, dust and soil samples collected near human habitats. However, no local study has yet to examine these amoebae in a forest, an isolated terrestrial environment, where human activity is relatively scarce. Further, there are also limited studies to investigate the same globally. The current study reported the isolation, morphological and genotypic characterisations of eleven Acanthamoeba sp. isolated from soils of the Payeh Maga Highland forest, Sarawak, Malaysia. Morphological analysis revealed that nine isolates belonged to Group II, whereas two isolates belonged to Group III as defined by the criteria of Pussard and Pons. The phylogenetic analysis based on complete 18S rRNA gene sequences showed that the isolates belonged to the rare T1 (six isolates), T6 (two isolates) and T13 (three isolates) genotypes. To the best of our knowledge, this is the first report about the detection of T6 Acanthamoeba sp. in this country. Overall, the current findings have enriched the knowledge pertaining to the occurrence, morphological and genotypic characteristics of Acanthamoeba sp. in an isolated terrestrial environment of Malaysia.